Enhancing Employee Performance through Strategic Training: A Study of the Food and Beverage Kitchen Department in Five-Star Hotel in Nusa Dua - Luh Putu Kartini; Prastha Adhyatma; Ni Luh Dita Priliani (Syntax Corporation Indonesia, 2024)
This study investigates the impact of training on employee performance in the Food and Beverage Kitchen Department of five-star hotels in Nusa Dua. The research aims to bridge the gap between theoretical models of training and their practical implementation within the hospitality sector. A quantitative descriptive methodology was employed, with data collected through online questionnaire. The data were analysed using SPSS version 23, including validity and reliability tests, simple linear regression, and t-tests. The results indicate a significant positive relationship between training and employee performance. The study concludes that effective training programmes are crucial for enhancing employee performance and recommends improving training methods and facilities. Future research could explore the long-term effects of different training types on performance outcomes.